Human brucellosis in a non-susceptible host: a case report - Chidambaram, Yoganathan; Alagesan, Murali; Dhas, Clement Jenil (International Journal of Advances in Medicine, 2018)
Clinical human brucellosis is quite rare in India, that too in an non susceptible host. This report describes a case of clinical human brucellosis in India. This case involved a 36 years old male, a professor in an Engineering college. He presented with complaints of fever for 4 months with myalgia, generalized tiredness, loss of weight and loss of appetite. On evaluation, total counts and ESR was elevated and all other investigations were normal. Based on history, common causes like occult tuberculosis or autoimmune diseases were considered. But, blood cultures grew Brucella melitensis in all 2 samples and a diagnosis of brucellosis was made. He was treated with Rifampicin and Doxycycline. Suspicion of brucellosis in this patient is low because the patient has no history of contact with animals, consumption of unpasteurized milk or occupational exposure. So, the health care practitioners should be aware of this possibility of this zoonotic infection as a differential diagnosis in patients with nonspecific symptoms and unexplained prolonged fever.